Human capital depreciation and education level. Issue 5 (29th July 2014) - Weber, Sylvain
Abstract : Purpose: – The purpose of this paper is to investigate the link between human capital depreciation and education level, with an emphasis on potential differences between general and specific education. Design/methodology/approach: – A nonlinear wage equation, based on Arrazola and de Hevia's (2004) model, is estimated using data from the Swiss Labor Force Survey (SLFS) over the period 1998-2008, in order to estimate a human capital depreciation rate for several education groups. Findings: – Human capital depreciation is significantly related to education type. Academic ("concept-based") education protects workers more effectively against depreciation than vocational ("skill-specific") education. Research limitations/implications: – The SLFS survey is a rotating panel of five years and no retrospective data on earnings and employment are provided. A study of lifecycle earnings like the one proposed here would clearly benefit from a longer individual observation period. Practical implications: – In all educational tracks, even vocational ones, a substantial time share should be devoted to the acquisition of general skills. Moreover, it is necessary to manage lifelong learning carefully in order not to waste initial investments in education. Originality/value: – Instead of using a purely quantitative approach to separate workers by years of education, qualitative aspects of educational system are taken into account. Taking advantage of the Swiss educational system characteristics, workers are separated on the basis of their education type. Workers with vocational education (apprenticeships, professional and technical schools and universities of applied sciences) are assumed to possess a relatively specific human capital, compared to those with academic education (high schools and universities).